Kompensasi Hijau: Gaji dan Manfaat Kesejahteraan Berkelanjutan Berbasis Kinerja Karyawan dalam Kewirausahaan Sosial Pengelolaan Sampah - Lukmana Putra, Indra; Wijayanto, Nugraha; Junus , Mochammad (UMSurabaya Publishing, 2025)
Green compensation, reward system for employee performance, is crucial for sustainability in organizations requiring human resources, including waste management social entrepreneurship. Social entrepreneurship, built on social intentions and goals, represents an innovative approach to addressing social problems while creating business opportunities. Social enterprises that empower surrounding communities, rewards are implemented through salaries and welfare benefits. Relationship between compensation, benefits, and employee performanced in waste management social entrepreneurship varies, with evidence showing that adequate compensation significantly enhances productivity and motivation. Particularly relevant in waste management, where employee engagement is essential for effective operations. Quantitative research aims to determine whether salary and welfare benefits influence employee performance in a waste management social enterprise.Research sample consists of 103 staff members who have been empowered by the organization, which has been in operation for over 12 years. Data were collected using a structured questionnaire distributed to all employees in the sample. Data were processed using statistical analysis software (such as SPSS) determine strength and significancy relationships between variables. Findings reveal salary and welfare benefits significancy impact on employee performance. However, magnitude influence falls within the moderate category, suggesting that other factors not examined in this study also affect performance. Additional factors warrant further investigation to provide a more comprehensive understanding of employee performance drivers